Pharmacological therapy in the management of temporomandibular disorders and orofacial pain: a systematic review and meta-analysis - Giuseppe Minervini; Rocco Franco; Salvatore Crimi; Marco Di Blasio; Cesare D'Amico; Vincenzo Ronsivalle; Gabriele Cervino; Alberto Bianchi; Marco Cicciù (BMC, 2024)
Abstract Background Temporomandibular disorders (TMD) are manifested by soreness in the jaw joint area and jaw muscles, clicks or creaks when opening or closing the mouth. All these symptoms can be disabling and occur during chewing and when the patient yawns or speaks. Several classes of drugs are used to treat symptoms. This review aims to assess which drug suits the different signs. Methods Pubmed, Web of Science and Lilacs were systematically searched until 01/02/2023. Clinical trials were selected that dealt with drugs used in temporomandibular dysfunction Results Out of 830 papers, eight studies were included. The Meta-Analysis with Continuous Outcomes with Pre-Calculated Effect Sizes resulted in the rejection that there is intergroup variability (p.0.74). Conclusions Treatment of orofacial pain is still a significant challenge for dentistry. We can conclude that there is no drug of first choice in the treatment of temporomandibular pain. However, the clinician must distinguish the type of pain and the aetioloic cause of the pain so that the patient can be treated and managed pharmacologically.